Environmental Hazard Identification Technique Developing of Territorial Administrations Strategy as Exemplified in Siberian Federal District; IOP Conference Series: Materials Science and Engineering; Vol. 127 : Urgent Problems of Modern Mechanical Engineering - Timofeeva S. S. (2016, 2016)
Title screen